Training Effectiveness and Return on Investment: Perspectives From Military, Training, and Industry Communities. (September 2016) - Moss, Jason D.; Brimstin, Jay A.; Champney, Roberto; DeCostanza, Arwen H.; Fletcher, J. D.; Goodwin, Gregory
In today's research and development, and training communities, return on investment (ROI) and training effectiveness (TE) are critical factors that need to be considered up-front, during, and post deployment of a training technology/platform or program. In the past, TE may have been viewed as a construct separate to ROI; however, today, viewing TE in the same sentence as ROI has been accentuated. Panelists will discuss current and/or past experiences with TE and/or ROI. Perspectives from the military, training, and industry communities will be represented. Some topics that will be discussed are: should ROI and TE be viewed as separate constructs or a synergy, group and team TE, return on training investment, and measures and outcomes of TE and ROI.